Robust range image registration : using genetic algorithms and the surface interpenetration measure - Silva, Luciano Afonso da, 1973- (Series in machine perception and artificial intelligence, 2005)
This book addresses the range image registration problem for automatic 3D model construction. The focus is on obtaining highly precise alignments between different view pairs of the same object to avoid 3D model distortions; in contrast to most prior work, the view pairs may exhibit relatively little overlap and need not be prealigned.